STUDENTS’ RESPONSES TOWARD THE IMPLEMENTATION OF THEME-BASED TEACHING IN EYL CLASS - Risma Rahmawati (Journal of English and Education, 2014)
This paper presents to report the research that was conducted to find out what the students’ responses were toward the activities presented in the classroom as the implementation of Theme-Based Teaching. This research was carried out to the third graders in one primary school in Bandung. Action research was conducted by managing classroom observation and interview to collect the data. Based on the research findings, it is revealed that the students responded to the reading activities presented in the classroom positively by actively participating in each activity. In accordance with the findings, it is suggested that teacher take into account the implementation of Theme-Based Teaching in teaching young learners since it leads to the positive response from the students. Keywords: Theme-Based Teaching, response, action research